Land, Women, Youths, and Land Tools or Methods - Chigbu, Uchendu Eugene (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a collection of Special Issue articles that aim to discern a people-centered pathway to solving land-based challenges in the context of land administration. It consists of 13 positively evaluated research articles. Each of the articles contributes to the large mosaic of knowledge on land methods (or tools) that are relevant to resolving land challenges that women and youths face. The book highlights 13 critical lessons on "Land, Women, Youths, and Land Tools or Methods."